2004
DOI: 10.1038/sj.leu.2403332
|View full text |Cite|
|
Sign up to set email alerts
|

Activation of the HIF pathway in childhood ALL, prognostic implications of VEGF

Abstract: Hypoxia-inducible factor 1 (HIF-1) controls angiogenesis and glycolysis, two leading characteristics of solid tumor invasion, metastasis, and lethality. Increased angiogenesis is also found in the bone marrow (BM) of leukemias. Less is known in leukemia about the role of HIF-1 and vascular endothelial growth factor (VEGF), the most important proangiogenic target gene of HIF-1. We show by immunohistochemistry that the oxygen-regulated component of HIF-1 (HIF-1a) is overexpressed in clusters of leukemic cells in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(52 citation statements)
references
References 44 publications
3
45
1
3
Order By: Relevance
“…10 Hypoxia-Inducible Factorα (HIF-1α), one of the best characterized markers of hypoxia, was shown to be overexpressed in clusters of BM-resident leukemic cells in pediatric ALL cases while absent in normal BM biopsies. 11 In agreement with this, we found high levels of HIF-1α in six of the nine BM biopsies obtained from ALL patients at the time of diagnosis that was reduced to low/undetectable levels in the paired BM samples obtained after patients have achieved complete remission. 10 HIF-1 is a key regulator of the cellular response to hypoxia 12 that is stabilized post-transcriptionally by levels of oxygen tension less than 2%.…”
Section: Examination Of Hif-1α Expression In Primary All Specimenssupporting
confidence: 88%
See 1 more Smart Citation
“…10 Hypoxia-Inducible Factorα (HIF-1α), one of the best characterized markers of hypoxia, was shown to be overexpressed in clusters of BM-resident leukemic cells in pediatric ALL cases while absent in normal BM biopsies. 11 In agreement with this, we found high levels of HIF-1α in six of the nine BM biopsies obtained from ALL patients at the time of diagnosis that was reduced to low/undetectable levels in the paired BM samples obtained after patients have achieved complete remission. 10 HIF-1 is a key regulator of the cellular response to hypoxia 12 that is stabilized post-transcriptionally by levels of oxygen tension less than 2%.…”
Section: Examination Of Hif-1α Expression In Primary All Specimenssupporting
confidence: 88%
“…10 In the current study, we have shown overexpression of HIF-1α in a large subset of newly diagnosed adult B-ALL cases, consistent with previously published data in pediatric ALL cases. 11 It should be noted, however, that HIF-1α levels in cell lysates prepared after exposure of cells to ambient O 2 levels may be reduced from the physiological conditions, given the very short (5-8 min) half-life of HIF-1α under normoxic conditions. Notably, HIF-1α was detectable at similar levels in paired peripheral blood and bone marrow samples from leukemia patients, possibly due to egress of hypoxic bone marrow blasts into the circulation, reported recently in a murine myeloma model.…”
Section: Discussionmentioning
confidence: 99%
“…from fluorine-18-fluorodeoxyglucose (FDG) positron emission tomography (PET), gene and protein expression profiling) that paediatric like adult tumours have a high glucose turnover and that anaerobic glycolysis might also be relevant for paediatric malignancies [18][19][20][21][22]. Furthermore, the expression of the four PDK isoforms and/or of antiapoptotic proteins, like Bcl-2, PUMA or survivin might have influenced the sensitivity to DCA [5,7].…”
Section: Discussionmentioning
confidence: 99%
“…38,39]. The goal was to identify cutoff point of VEGF-A concentrations as an optimal pharmacodynamic predictor parameter that had both ''high sensitivity'' and ''high selectivity'' at the same time.…”
Section: Methodsmentioning
confidence: 99%